Analytical methods for nanomaterials investigation in food and food-related materials - Daniele Passeri; Pierfrancesco Atanasio; Anacleto Proietti; Chiara Mancini; Flavio Cognigni; Giancarlo La Penna; Luca Buccini; Marco Rossi; Anna Chiara Turco; Marilena D'Amato; Angela Sorbo; Simone Dinarelli; et al. (Applied Food Research)
The use of engineered nanomaterials is widely distributed throughout the whole food chain to improve yield, durability, taste, and appearance of commercialized food. Moreover, nanotechnology stepped into the world of food packaging, granting better conservation of foods, avoiding bacterial contaminations, or reducing the spoiling of nutritive substances. All these improvements, however, need to be achieved in a ‘safe’ way, thus there is a wide and constantly updated legislation that deals with the possible toxicity of these additions by posing some limitation to the percentage of nanosized elements added and to their composition. Thus, the characterization of the nanomaterials ‘in situ’, e.g., directly inside the biological matrix, is of paramount importance, to measure the real concentration of the nanomaterials as well as their distribution and unwanted local modification of the biological matrix. Here we review the main high-resolution techniques that are currently used for these characterizations in combination with the most up-to-date analytical methods, i.e., X-ray (X-ray microscopy and X-ray diffraction), scanning microscopies (electron microscopy and atomic force microscopy), optical spectroscopies (infrared spectroscopy and Raman spectroscopy), and mass spectrometry, discussing their benefits and drawbacks. Some important results are reported and their applications are discussed not only in the characterization of nanosized objects deliberately added to the food and food packaging to improve their properties, but also in the characterization of unwanted nano-sized and micro-sized objects that originate from possible environmental contamination that can happen at every step of the food chain starting from water. Among them, the characterization of micro- and nano-plastics and some nanosized metallic pollutants using these analytical techniques is discussed.